Promoting self-change in cannabis use disorder: Findings from a randomized trial - Schluter, Magdalen G.; Hodgins, David C.; Stea, Jonathan N.; Kilborn, Michelle L. (Frontiers in Psychiatry, 2022)
Background: A growing body of literature supports the efficacy of cognitive-behavioural therapy (CBT) and motivational interviewing (MI) for the treatment of problematic cannabis use, diagnostically referred to as cannabis use disorder, though most individuals do not access formal treatment. Stepped-care-type models emphasize interventions across a continuum of severity and there is a need for more treatment options across this continuum. This project focused on the evaluation of the least intensive of the individual interventions – promotion of self-directed recovery. Methods: Using a three-arm randomized control trial design, adults (N = 186) with problematic cannabis use and who wished to recover with minimal professional support were recruited from across Canada and randomized to receive a self-directed treatment workbook based on CBT and MI principles (WB; n = 61), the workbook plus a single MI session (WMI; n = 61) or a delayed treatment control (DT; n = 65) condition. Participants completed 3-month and 6-month follow-up assessments. Results: Across conditions, GEE modeling revealed that the baseline to 3-month slopes differed significantly from zero, ps < .001. Participants in the WMI condition reduced their frequency of use to a greater extent than the WB alone, p = .005, and DT groups, p =.02. Chi-square analysis revealed that participants in the WMI condition also showed greater rates of abstinence at 3-months follow-up than participants in the WB or DT condition, p = .046. Changes in the frequency of cannabis use between 3-months and 6-months did not differ significantly between groups, ps > .05. For quantity of cannabis use, a significant effect of time emerged, p = .002. However, no between-group effects were significant from baseline to 3-months, or from 3- to 6-months, ps > .06. Conclusion: Overall, results support the utility of a brief self-directed workbook in combination with a single MI session at promoting changes in cannabis use. This self-directed intervention has the potential to fill an important need in that the self-directed intervention can attract individuals who wish to recover with minimal professional support. This trial is registered with the ISRCTN registry (https://www.isrctn.com/ISRCTN42632893).